Unbiased Phenotype-Based Screen Identifies Therapeutic Agents Selective for Metastatic Prostate Cancer - Chung, Ivy; Zhou, Kun; Barrows, Courtney; Banyard, Jacqueline; Wilson, Arianne; Rummel, Nathan; Mizokami, Atsushi; Basu, Sudipta; Sengupta, Poulomi; Shaikh, Badaruddin; Sengupta, Shiladitya; Bielenberg, Diane R.; et al. (Frontiers in Oncology, 2021)
As with many solid tumors, the prognosis for prostate cancer patients worsens when tumors metastasize to distant organs, such as the bone. Current chemotherapy is relatively limited for metastatic prostate cancer. To identify drugs selective for metastatic cells, a phenotype-based screening method consisting of multiple panels of highly and weakly metastatic prostate cancer cell lines were used to identify compounds that selectively targeted metastatic prostate cancer cells over benign prostate cancer cells and normal prostate epithelial cells. Selected agents from a library of 1120 FDA-approved drugs were then tested in various in vivo models including subcutaneous tumor growth, experimental lung metastasis, and experimental bone metastasis for their ability to improve survival time in mice. Lead candidates which showed selective cytotoxicity toward metastatic prostate cancer cells in vitro and in vivo included: fenbendazole, fluspirilene, clofazimine, niclosamide and suloctidil. These drugs showed selective induction of apoptosis in metastatic prostate cancer cells. The bioavailability of the most discerning agents was improved by formulating as micelles or nanoparticles. Upon improvement in bioavailability, fenbendazole and albendazole significantly extended the survival of metastases-bearing mice; and the extension in lifespan by albendazole was greater than that provided by paclitaxel. These drugs were also active in taxane-resistant tumors and in the bone microenvironment--two clinical conditions of men with advanced prostate cancer. Overall, we conclude that metastatic prostate tumor cells differ in their sensitivity to certain drug classes. Albendazole, an anthelmintic medication, showed promise as a potential adjuvant to standard therapy in metastatic prostate cancer models.